Simulasi kontur distribusi suhu dan kecepatan fluida pada heat exchanger type shell and tube aliran dua stage sistem counter flow dengan computational fluid dynamics (cfd) - Achmad Ramadhan Muzaki; Fajar Anggara (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2022)
The simulation of temperature and velocity distribution contours is designed to produce output regarding the capability and reliability of the shell and tube heat exchanger system, as input in the framework of assessing system development and optimization of operating results. This research was conducted numerically with a variation of hot fluid input flow of 0.8 kg / second and a cold fluid input flow of 1 kg / second and variations in hot inlet temperatures: 60 ° C, 90 ° C, 120 ° C, cold temperature inlet variations: 15 ° C, 16 ° C, 18 ° C using the Computational Fluid Dynamics (CFD) method on the ANSYS software. In this study, the design contours of the temperature and velocity of the outlet of hot fluid and outlet of cold fluid can be determined with the following variation results: the contour of the temperature distribution of hot fluid is seen on the lowest part of the wall which has a blue color and the highest has a red color, while the cold fluid shows a temperature. the lowest is dark blue and the highest temperature is light blue. The velocity distribution contours of hot and cold fluids can be seen on the lowest part of the wall which has a blue color and the highest has a yellow green color.